An Evaluatıon Of Occlusıon Of Chıldren In The Prımary And Mıxed Dentıtıon - Halil Kayalıbay; Meryem Uzamış; Gülgün İkören (Galenos Yayinevi, 1996)
The occlusion in the primary and mixed dentition stages have evaluated. Among the children being examined, highest rates for class 1 incisor occlusion, flush terminal plane in decidious dentition and class 1 molar occlusion in permanant molars found as 72% 46% and 15,5% respectively. No significant differences between sex.